(untitled) (Eurasian Journal of Ecology, 2016)
The paper discusses the status and problems of the transition to sustainable development. The analysis and the necessity of immediate construction in Kazakhstan "green economy." Based on the theory and taking into account the similar experience of advanced countries to provide direction, the ways and mechanisms of selected acceleration.